2018
DOI: 10.20546/ijcmas.2018.708.206
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Rice: Smart Technology of Rice Cultivation

Abstract: Rice is one of the most important food crops that feed over half of the global population and biggest consumer of fresh water diverted from irrigation. Water scarcity is burning issue of agriculture, outcome of climate change and unpredictable rainfall. It threatens the future of irrigated rice cultivation. Researchers developed new technology called -Aerobic Rice‖ to cope up with present situation. Rice is grown in well-drained, non-puddled and non-saturated soils. Aerobic rice cultivar has drought tolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Some upland rice varieties have been observed to be adapted in aerobic condition due to their droughtresistant characteristics, but these do not attain similar yield as the high-yielding lowland varieties. Recent studies in aerobic rice breeding programs have indicated that in order for rice varieties to be suitable for aerobic cultivation, new genotypes which possess both the vigorous root growth of upland varieties for drought tolerance, combined with the high-input responsiveness of lowland varieties for high yield must be developed (Dey et al, 2018;Du et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some upland rice varieties have been observed to be adapted in aerobic condition due to their droughtresistant characteristics, but these do not attain similar yield as the high-yielding lowland varieties. Recent studies in aerobic rice breeding programs have indicated that in order for rice varieties to be suitable for aerobic cultivation, new genotypes which possess both the vigorous root growth of upland varieties for drought tolerance, combined with the high-input responsiveness of lowland varieties for high yield must be developed (Dey et al, 2018;Du et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another significant benefit of cultivating aerobic rice is preventing the loss of essential micronutrients from the soil and decreasing methane gas emissions as a product of flooded fields [ 11 ]. In this perspective, Liu et al [ 8 ], Sandhu et al [ 12 ], Fukai and Mitchell [ 13 ], Dey et al [ 14 ] and Bhutto et al [ 15 ] explained that aerobic rice cultivation represents an innovative and sustainable approach to rice farming that significantly diverges from traditional methods. It primarily addresses water scarcity in rice cultivation by promoting water efficiency and reducing the dependency on flooded conditions typically associated with paddy rice farming.…”
Section: Introductionmentioning
confidence: 99%
“…Rice ( Oryza sativa L.) is an essential staple crop that secures food for almost two-thirds of the world's population 1 . The cultivation of rice occupies about twenty percent of the agricultural land area planted for cereals 2 . In Egypt, rice production faces many grand challenges such as freshwater scarcity, salt stress, the high cost of inputs, and overpopulation.…”
Section: Introductionmentioning
confidence: 99%